Научно-технический русский язык: учебное пособие - Хань Вэй; Выдрина В. В. Вера Владимировна; Курикова Н. В. Наталья Владимировна; Пустынников С. В. Сергей Владимирович; Русинова Н. С. Наталия Сергеевна; Чапля В. В. Вера Владимировна; Шандарова Е. Б. Елена Борисовна; Чжан Лиян (Чанчунь, Изд-во Цзилиньского университета, 2015)
Заглавие с титульного экрана